PROFITABILITAS MEMODERASI PENGARUH OPERATING CAPACITY, KEPEMILIKAN MANAJERIAL, DAN OPERATING CASH FLOW TERHADAP FINANCIAL DISTRESS - Angela Audina Puspita, (2022)
This research is a quantitative study that aims to determine the effect of operating capacity, managerial ownership, and operating cash flow towards financial distress, moderated by profitability, and with leverage and firm age as control variables. Financial distress as a dependent variable in this study is measured using the modified Altman Z-Score for non-manufacturing companies (1995 version). The samples used in this study are 31 mining companies that are listed in the Indonesian Stock Ecxhange (IDX) during the period of 2017-2021. Multiple linear regression and panel data regression were used as the analysis techniques using STATA 16 with a significance level of 5%. The results of this study show that (1) operating capacity does not have a significant effect towards financial distress. (2) managerial ownership has a positive-significant effect towards financial distress (3) operating cash flow has a positive-significant effect towards financial distress (4) profitability is not able to moderate the relationship between operating capacity and financial distress. (5) profitability is not able to moderate the relationship between managerial ownership and financial distress. (5) profitability is not able to moderate the relationship between operating cash flow and financial distress.